Presentation: Ethnicity in the Old Regime - Allpanchis, Revista (2008)
The historiographical context of the bicentennial of the Hispano-American independence has oriented the gaze of historians to the political-cultural panorama of the so-called Old Regime, a term used by the French revolutionaries to refer to the social order entirely different from the republican system, built in a rationally utopian manner on the liberal principles. Indeed, the construction of the nation-state entailed a radical change in the political forms and cultural assumptions on which a three-century political order had been built, with strong and lasting representations and imaginaries that legitimized a Catholic monarchy, a body composed of civil and canon laws, and a concept of justice that presupposed the recognition of ethnic and class differences to exercise justice according to the state and condition of each one.